Collective plasmonic resonances enhance the photoluminescence of rare-earth nanocrystal films processed by ultrafast annealing. Issue 10 (16th January 2023) - Cabello-Olmo, Elena; Higashino, Makoto; Murai, Shunsuke; Tanaka, Katsuhisa; Lozano, Gabriel; Míguez, Hernán
Abstract : Rapid thermal annealing allows ultrafast processing of rare-earth nanocrystal thin films to achieve close-to-one photoluminescence quantum yield while preserving the transparency of the layers, which further enables their integration with photonic architectures. Abstract : Herein, we demonstrate that rapid thermal annealing allows achieving close-to-one photoluminescence quantum yield while preserving the transparency of rare-earth nanocrystal films, which further enables their integration with nanophotonics. The combination with periodic arrays of aluminum nanodisks that support collective plasmonic resonances leads to enhanced directional emission.